Peristiwa Perebutan Gedung Sate di Bandung Tahun 1945 - Sulasman Ai Latifah Fathia Lestari (Jurnal Tamaddun, 2022)
In the midst of the chaotic situation in the raging revolution in 1945, a number of battles that occurred also colored the course of the revolutionary period in Bandung. The battle between the Allied troops and Indonesian troops to defend Gedung Sate was one of them. The method used in this study is the historical method, namely heuristics, criticism, interpretation and historiography which are divided into four stages. The concept used in this study refers to the conflict theory proposed by the American sociologist, Lewis A. Coser. The building which was built in 1920 was originally used for the Verkeer en Watertaat Department, where its construction became a project of the Dutch East Indies Government to relocate the administrative center from Batavia (Jakarta) to Bandung. On December 3rd, 1945, Gurkha troops (British mercenaries supported by NICA) came storming when the building was only defended by 21 youth employees of the Public Works Department (PU). The battle was fierce until in the end due to unbalanced forces, the youths were defeated and Gedung Sate managed to fall into the hands of the enemy. Its strategic value is the NICA reason to seize Gedung Sate.